2012
DOI: 10.1136/bcr-2012-007187
|View full text |Cite
|
Sign up to set email alerts
|

Successful laparoscopic investigation and resection of solitary colonic metastasis from breast cancer (with video)

Abstract: Metastasis to gastrointestinal tract from breast cancer is an uncommon situation. We report a case of a 52-year-old woman who had a mastectomy for solid-tubular carcinoma of the breast 16 years ago and bilateral salpingo-oophorectomy for metastatic ovarian tumours 5 years ago, was incidentally found to have colonic metastatic tumour detected by positron emission tomography/CT (PET/CT) during follow-up. After identifying a definite location of the tumour in the ascending colon under laparoscopic investigation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Chang et al reported that a long period of time was sometimes required for metastasis to the GI tract after breast cancer surgery (11); however, the underlying mechanisms remain unclear. We searched PubMed and, to the best of our knowledge, only 15 cases were reported from 2010, including the present case, for the surgical resection of CMBC 10 years or more after primary breast cancer resection (Table I) (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). In these reports, and the present case, a long period of time had elapsed following breast cancer surgery, which made it difficult to diagnose CMBC prior to its resection.…”
Section: Discussionmentioning
confidence: 99%
“…Chang et al reported that a long period of time was sometimes required for metastasis to the GI tract after breast cancer surgery (11); however, the underlying mechanisms remain unclear. We searched PubMed and, to the best of our knowledge, only 15 cases were reported from 2010, including the present case, for the surgical resection of CMBC 10 years or more after primary breast cancer resection (Table I) (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). In these reports, and the present case, a long period of time had elapsed following breast cancer surgery, which made it difficult to diagnose CMBC prior to its resection.…”
Section: Discussionmentioning
confidence: 99%